Niemann–Pick type C disease: cellular pathology and pharmacotherapy. Issue 6 (15th November 2019) - Wheeler, Simon; Sillence, Dan J.
Abstract: Niemann–Pick type C disease (NPCD) was first described in 1914 and affects approximately 1 in 150 000 live births. It is characterized clinically by diverse symptoms affecting liver, spleen, motor control, and brain; premature death invariably results. Its molecular origins were traced, as late as 1997, to a protein of late endosomes and lysosomes which was named NPC1. Mutation or absence of this protein leads to accumulation of cholesterol in these organelles. In this review, we focus on the intracellular events that drive the pathology of this disease. We first introduce endocytosis, a much‐studied area of dysfunction in NPCD cells, and survey the various ways in which this process malfunctions. We briefly consider autophagy before attempting to map the more complex pathways by which lysosomal cholesterol storage leads to protein misregulation, mitochondrial dysfunction, and cell death. We then briefly introduce the metabolic pathways of sphingolipids (as these emerge as key species for treatment) and critically examine the various treatment approaches that have been attempted to date. Abstract : Mutations in lysosomal export protein NPC1 have unexpectedly widespread consequences for the life of the cell. These are summarized and integrated in the present Review. The diverse approaches to therapy taken so far are surveyed.